OXYGEN AND SULFUR ISOTOPE FRACTIONATION DURING ANAEROBIC BACTERIAL DISPROPORTIONATION OF ELEMENTAL SULFUR - Bottcher M.E.; Thamdrup B.; Vennemann T.W. (My University, 2001)
Bacterial disproportionation of elemental sulfur is an important process in the sulfur cycle of natural sediments and leads to the formation of hydrogen sulfide and sulfate. The oxygen atoms in sulfate during this anaerobic process are completely derived from water according to the overall reaction: 4H2O + 4S0 -> 3H2S + SO42- + 2H+In the present study, stable oxygen isotope fractionation during formation of sulfate via this reaction was experimentally investigated for a pure culture (Desulfocapsa thiozymogenes) and an enrichment culture (''Kuhgraben'') at 28°C. Synthetic FeCO3 and FeOOH were used as scavengers for hydrogen sulfide to keep the disproportionation reaction exergonic and to suppress polysulfide formation and isotope exchange between elemental sulfur and hydrogen sulfide. Compared to water, dissolved sulfate was enriched in 18O by +17.4 +/- 0.1%% (Desulfocapsa thiozymogenes) and +16.6 +/- 0.5%% (Kuhgraben) at cell specific sulfur disproportionation rates of 10-15.4 +/- 0.4 mol S° cell-1 h-1 and 10-14.4 +/- 0.9 mol S° cell-1 h-1, respectively. Oxygen isotope fractionation was not influenced by the type of iron-bearing scavenger used, corroborating earlier findings that H2S oxidation by FeOOH yields elemental sulfur as the dominant oxidation product. Sulfite is suggested to be formed as a metabolic intermediate to facilitate isotope exchange with water. Due to bacterial disproportionation, dissolved sulfate was also enriched in 34S compared to elemental sulfur by +11.0 to +18.4%% (D. thiozymogenes) and +12.7 to +17.9%% (Kuhgraben). FeS was depleted in 32S compared to elemental sulfur by -3.7 to -5.3%% (D. thiozymogenes).